Automatic Separation of Awakening from Sleep Epochs based on Bispectrum Analysis of Electroencephalogram Signals - Ehsan Mohammadi; Saeed Kermani; Babak Amra (مجله دانشکده پزشکی اصفهان, 2017)
Background: Accurate separation of awakening from sleep increases the accuracy of detecting sleep stages and determining sleep efficiency index that is important for medical diagnosis. In this study, 3 new bispectrum-based features were extracted, and combination of them with Bi-Phase correlation was used to detect awakening from sleep.